Organochlorine Pollutants within a Polythermal Glacier in the Interior Eastern Alaska Range - Kimberley R. Miner; Seth Campbell; Christopher Gerbi; Anna Liljedahl; Therese Anderson; L. Brian Perkins; Steven Bernsen; Tiffany Gatesman; Karl J. Kreutz (Water, 2018)
To assess the presence of organochlorine pollutants (OCP) in Alaskan sub-Arctic latitudes, we analyzed ice core and meltwater samples from Jarvis Glacier, a polythermal glacier in Interior Alaska. Jarvis Glacier is receding as atmospheric warming continues throughout the region, increasing opportunity for OCP transport both englacially and into the proglacial watershed. Across glacial meltwater and ice core samples, we utilize solid-phase extraction technology and identify the pesticides DDT, DDE and DDD, α-HCH and γ-HCH. OCP concentrations in ice core samples were highest at the 7–14 m depth (0.51 ng/L of DDT) and decreased gradually approaching the bedrock at 79 m. Meltwater concentrations from the proglacial creek slightly exceeded concentrations found in the ice core, potentially indicating aggregate OCP glacial loss, with peak OCP concentration (1.12 ng/L of DDD) taken in July and possibly associated to peak melt. Ongoing use of DDT to fight malaria in Asia and the extended atmospheric range of HCH may account for concentrations in near-surface ice of this remote glacier, correlating with use and atmospheric transport. The opportunity for bioaccumulation of OCPs, in humans or animals, of glacially distributed pollutants may increase as glacial melt continues.